Orcein and DAPI-stained karyotype analysis of Alocasia macrorrhizos (L.) G. Don (Journal of Bangladesh Academy of Sciences, 2021)
Karyotype analyses are required for the identification, characterization, and genetic improvement of any organism. Alocasia macrorrhizos (L.) G. Don. was investigated cytogenetically to determine the karyotypic features. Complex chromocenter type, of interphase nuclei, and gradient type of prophase chromosomes were found in this study. Alocasia macrorrhizos was found to possesses 2n=28 chromosomes. The total length of the 2n chromosome complement was recorded as 98.83±1.39 μm. The range of chromosomal length was 2.50±0.10-4.70±0.10 μm. A gradual decrease in chromosomal length was observed. The total form (TF%) value was found to be 43.58%, Karyotype symmetry index (Syi %) was 77.00 % and karyotype asymmetry index (AsK %) was 56.66%. The centromeric formula was 18m+4sm+2ac, representing asymmetric karyotype. In DAPI banding, the 1.48% positive banded region indicates the lower amount of AT rich repeats in this material. Therefore, Alocasia macrorrhizos could be authentically characterized through karyotype analysis.J. Bangladesh Acad. Sci. 45(1); 27-35: June 2021